A Clinical Study to Evaluate the Effectiveness of ( Er:YAG Laser ,Novamine ) , on Remineralization of Incipient Enamel Lesions in young (Journal of Hama University, 2022)
Evaluate the effectiveness of Er:YAG Laser and Novamine on remineralizing primary enamel lesions of young permanent teeth.The sample consisted of 40 young anterior teeth from patients with primary enamel lesions.The sample was randomly divided into two groups: A group on which the Novamine-containing paste was applied using a rubber funnel on the micromotor grip in a clockwise direction for 1 minute, A group on which an Er:YAG laser with a wavelength of 2040 nm was applied, at a fixed distance of 2.5 cm from the lesion, with a scanning movement for 30 seconds.The treatment phase was followed by observational sessions (immediately, three months later, and six months later).To assess the color improvement: Pictures were taken with a professional camera (canon 80 D) and a (sigma 105 mm) lens. The method of measuring digital image analysis was relied upon using Photoshop, version (21.0.3 2020).The results showed that there were no significant statistical differences in the amount of chromatic improvement before and after treatment and even after three months. Whereas, significant statistical differences were found between the two groups after six months.The amount of remineralization after applying the paste containing Novamine was not fixed , it was just evident after three months of application, while the value of the color improvement after applying the Er:YAG laser was evident after six months of application